Self-rated health, time of residence and social determinants of health in immigrant populations: A complex relationship in groups of different origins in a Southern European region - Antía Domínguez-Rodríguez; Yolanda González-Rábago (Elsevier, 2024)
Health of immigrant population changes with time of residence and under the effect of social determinants of health. This study analyses the health status of the immigrant population in the Basque Country according to groups of origin assessing the effect of time of residence on health in the different origin groups considering social and migration-related determinants of health. A cross-sectional study of the immigrant population in the Basque Country using the Foreign Origin Population Survey was conducted. A descriptive analysis is performed of each group of origin and Poisson models are applied. The main variable is self-rated health, and the independent variables are divided into three groups: demographic, socioeconomic and migration-related. For the study, immigrants are divided into six origin groups. Results show that the health and the effects of socioeconomic and migratory variables on health vary according to origin. Immigrants with greater economic difficulties present poorer health, though to different extents and the effects on health of educational level and perception of discrimination differ according to origin. Finally, the relation between time of residence and self-rated health varies according to origin: Colombian, Ecuadorian, Peruvian, Eastern EU and sub-Saharan immigrants living in Spain for 10 or more years report poorer health even when controlling for socioeconomic and migration-related variables, while people from the Maghreb and Asia do not. Therefore, the effects on health of time of residence, living conditions and the migratory experience differ according to migrant group, leading to the importance of analysing the health of immigrants as a heterogeneous group.